Associations of childhood maltreatment with hypertension in South African women: a cross-sectional study. Issue 9 (19th September 2022) - Nguyen, Kim Anh; Kengne, Andre Pascal; Abrahams, Naeemah; Jewkes, Rachel; Mhlongo, Shibe; Peer, Nasheeta
Abstract : Objectives: To examine the associations of childhood maltreatment (CM) with hypertension, and the mediating effects of hypertension risk factors on the associations in South African women, using baseline data of the Rape Impact Cohort Evaluation longitudinal study. Design: Cross-sectional Setting and participants: Self-reported data on CM exposure and its severity in 18–40-year-old women living in KwaZulu-Natal province were assessed. Logistic regression models, adjusted for traditional hypertension risk factors, rape exposure, HIV-infection, other traumatic exposures, depression scores and acute stress reactions (ASR) scores were used to examine the CM–hypertension associations. Results: Among 1797 women, 220 (12.2%) had hypertension; CM prevalence was higher in women with hypertension than without hypertension overall (70.9% vs 57.2%) and for each abuse type: sexual abuse (20.9% vs 12.4%), physical abuse (51.8% vs 41.5%), emotional abuse (40% vs 27.6%) and parental neglect (35% vs 25.7%). Exposures to 1–2 types and 3–4 types of CM were 46.4% and 24.5%, respectively, in women with hypertension, and lower in women without (42.9% and 14.3%, respectively). Exposures to any CM (adjusted OR: 1.62; 95% CI: 1.19 to 2.25), sexual abuse (1.64; 95% CI: 1.12 to 2.37), emotional abuse (1.57; 95% CI: 1.16 to 2.13), physical abuse (1.43; 95% CI: 1.07 to 1.92) and parental neglect (1.37; 95% CI: 1.00 to 1.86) were associated with hypertension. Exposures to an increasing number of abuse types and cumulative severity of CM overall (1.13; 95% CI: 1.05 to 1.21) and for each CM type were associated with increased odds of hypertension. Alcohol use, other trauma experienced, depression and ASR partially mediated these associations. Conclusion: CM was associated with hypertension; the effects were greater with multiple abuse types and severe abuse, and were partially mediated by alcohol use, depression, ASR and other traumatic exposures. While CM must be prevented, effective mental health interventions to curb the uptake of unhealthy behaviours and the development of hypertension in women exposed to CM are key.